Marble season - Hernandez, Gilbert. (Drawn & Quarterly, 2013)
Middle child Huey stages Captain America plays and treasures his older brother's comic book collection almost as much as his approval. "Marble Season" subtly and deftly details how the innocent, joyfully creative play that children engage in (shooting marbles, backyard performances, and organizing treasure hunts) changes as they grow older and encounter name-calling naysayers, abusive bullies, and the value judgments of other kids. An all-ages story, "Marble Season" masterfully explores the redemptive and timeless power of storytelling and role play in childhood, making it a coming-of-age story that is as resonant with the children of today as with the children of the sixties.